Installation of the superconducting gravimeter CT(#043) at Syowa Station, Antarctica - Ikeda, Hiroshi; Doi, Koichiro; Fukuda, Yoichi; Tamura, Yoshiaki; Shibuya, Kazuo (National Institute of Polar Research, 2005)
P(論文) During the wintering period of the 44th Japanese Antarctic Research Expedition (JARE-44: February 2003 to January 2004), a new superconducting gravimeter CT(#043) with a cryocooler was installed and tested to replace the former TT70(#016) at Syowa Station, Antarctica. The CT(#043) has design sensitivity of 1nGal (1×10^(-11)m/s^2) to study the Earth's dynamics in tidal and longer-period bands. A new type of diaphragm was used to effectively isolate the vibration from the refrigerator cold-head and to prevent solid air contamination from entering the Dewar. A real-time remote monitoring system including a Web camera for diagnostics from Japan has also been installed. departmental bulletin paper